2003
DOI: 10.1007/s00049-003-0242-4
|View full text |Cite
|
Sign up to set email alerts
|

Receptor neurones in three heliothine moths responding to floral nd inducible plant volatiles

Abstract: Some plant volatiles are produced in response to herbivory of several insect species, including heliothine larvae. In the present study of female heliothine moths, four co-located receptor neurone types were identified, of which three types responded strongest to the inducible compounds E-β-ocimene, E,E-α-farnesene and E,E-TMTT, respectively. The fourth type responded strongest to geraniol, which is a common floral volatile. The narrow tuning of each receptor neurone type was demonstrated by responses to a few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 48 publications
5
44
0
Order By: Relevance
“…These concentration differences in learning performance may be partly due to a higher sensitivity of the moth olfactory system to linalool than to the other two odorants, as was indicated by the significant correlation of learning rate with the amplitude of EAGs recorded in Experiment 4 (Fig.·3). This finding is also in accordance with the increased responses to higher odorant concentrations obtained from single RNs measured by electrophysiological recordings (Stranden et al, H. T. Skiri and others (Skiri et al, 2004;Stranden et al, 2003b). Since single-cell recordings have shown similar sensitivities of the RN types to their primary odorants (Stranden et al, 2003b), the present EAG recordings may indicate that H. virescens has a higher number of RNs responding to linalool than to the other two odorants.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These concentration differences in learning performance may be partly due to a higher sensitivity of the moth olfactory system to linalool than to the other two odorants, as was indicated by the significant correlation of learning rate with the amplitude of EAGs recorded in Experiment 4 (Fig.·3). This finding is also in accordance with the increased responses to higher odorant concentrations obtained from single RNs measured by electrophysiological recordings (Stranden et al, H. T. Skiri and others (Skiri et al, 2004;Stranden et al, 2003b). Since single-cell recordings have shown similar sensitivities of the RN types to their primary odorants (Stranden et al, 2003b), the present EAG recordings may indicate that H. virescens has a higher number of RNs responding to linalool than to the other two odorants.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is also in accordance with the increased responses to higher odorant concentrations obtained from single RNs measured by electrophysiological recordings (Stranden et al, H. T. Skiri and others (Skiri et al, 2004;Stranden et al, 2003b). Since single-cell recordings have shown similar sensitivities of the RN types to their primary odorants (Stranden et al, 2003b), the present EAG recordings may indicate that H. virescens has a higher number of RNs responding to linalool than to the other two odorants. In addition, the EAG and calcium imaging experiments showed somewhat stronger responses to β-ocimene than to β-myrcene, the two compounds known from electrophysiological recordings to activate the same RN type, β-ocimene being the primary and β-myrcene a secondary odorant (Røstelien et al, 2000b;Stranden et al, 2003b).…”
Section: Discussionsupporting
confidence: 91%
“…appear to have a particularly pronounced ability to separate chemically similar odorants in their ALs. Accordingly, single-sensillum recordings revealed only narrowly tuned odorant receptor types in S. littoralis and other noctuid species (Anderson et al, 1995;Rostelien et al, 2005;Stranden et al, 2003), but both narrowly and broadly tuned receptor profiles in M. sexta (Shields and Hildebrand, 2000). A higher number of tested species representing each of the sphingid and noctuid subfamilies would of course be necessary to determine whether this difference is a consistent family-specific feature or only accidental, based on an unintentional bias in the selection of species.…”
Section: Discussionmentioning
confidence: 97%
“…Recent comparative studies revealed OSNs with mainly conserved receptive ranges or conserved representation patterns of odorants in the first olfactory neuropil across species, with only little impact of speciesspecific life histories. In these studies, however, only species belonging to the same family [Nymphalidae (Carlsson et al, 2011;Ômura and Honda, 2009)], subfamily [Heliothinae (Rostelien et al, 2005;Stranden et al, 2003); Murinae (Johnson et al, 2009;Soucy et al, 2009)], or genus [Drosophila (de Bruyne et al, 2010;Stensmyr et al, 2003)] were investigated. Remarkable similarities in olfactory coding were also found across the ant Camponotus fellah, the bee Apis mellifera and the rat Rattus norvegicus, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the LFGs might play important roles in the selection of appropriate sites for oviposition. Projection (output) neurons (PNs) with dendritic arborizations restricted to one of these glomeruli, the lateral LFG (latLFG), respond preferentially to the (ϩ) enantiomer of linalool (Reisenman et al, 2004), a plant volatile [Stranden et al (2003) and references therein]. Little is known, however, about the chemosensory tuning and functional properties of individual PNs in identified, sexually isomorphic glomeruli in the main AL of Manduca or other species.…”
Section: Introductionmentioning
confidence: 99%